2018
DOI: 10.1111/dmcn.13930
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of chronic pain in cerebral palsy: implications for pharmacological treatment and research

Abstract: Pain conditions in cerebral palsy have differing mechanisms and will not respond to the same treatments. Novel analgesics under development include inhibitors of ion channels, nerve growth factor, and calcitonin gene-related peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…Recognition is only half the battle. As stated by Blackman et al, recognition of pain is step one in our understanding of its underlying pathophysiology in young people with CP. In turn this may aid us in focusing on appropriate and potentially novel ways of pharmacological and therapeutic intervention to enable comfort and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition is only half the battle. As stated by Blackman et al, recognition of pain is step one in our understanding of its underlying pathophysiology in young people with CP. In turn this may aid us in focusing on appropriate and potentially novel ways of pharmacological and therapeutic intervention to enable comfort and function.…”
Section: Discussionmentioning
confidence: 99%
“…We were interested in what treatments individuals use to control pain, because Westbom et al found that in clinical practice, although structured assessments had captured the presence of pain, very little intervention was recorded in the notes of the young people. The implications of pharmacological treatment in chronic pain in CP were also highlighted in the recent review on pathophysiology by Blackman et al To address these questions, we report the presence, severity, timing, site, impact, associated features, and self‐management of pain in a cross‐sectional study of a population‐based cohort of young people with bilateral CP.…”
mentioning
confidence: 97%
“…The studies we have identified are mainly focused on nociceptive mechanisms and primarily in the musculoskeletal system. Chronic pain in CP is, however, complex and heterogeneous, involving multiple inhibitory and excitatory mechanisms in the peripheral and central nervous systems that may serve to increase pain experience or conversely offer potential targets for treatment . We identified no studies that examined treatment targeted to central pain excitatory mechanisms such as central sensitization, and suggest that these would be a valuable focus for future research.…”
Section: Discussionmentioning
confidence: 99%
“…We identified no studies that examined treatment targeted to central pain excitatory mechanisms such as central sensitization, and suggest that these would be a valuable focus for future research. Affective mechanisms are also important in the maintenance of chronic pain conditions and in their treatment …”
Section: Discussionmentioning
confidence: 99%
“…surgery) interventional management, general health conditions (e.g. headaches, period pain), and other CP related comorbidities [10,11]. CP related comorbidities are characteristically high in predominant dyskinetic subtypes, and may include scoliosis, hip displacement, muscle contracture, gastrointestinal dysfunction, and the dyskinetic movement disorder itself [10,12,13].…”
mentioning
confidence: 99%